Communication barriers and the need for support for deaf children in some specialized educational institutions in Vietnam: Deaf children's communication barriers and need - Thi Minh Phuong Tran; Thi Thai Lan Nguyen (Indonesian Social Work Consortium (ISWC), 2026)
Deaf children encounter significant challenges in communication that affect their learning, psychological well-being, and social integration, particularly in contexts where adequate support systems are limited. This study examines the communication barriers experienced by deaf children in specialized educational institutions in Vietnam. Using a mixed-methods approach, quantitative data were collected from 149 deaf students from two specialized educational institutions in Lam Dong Province; and qualitative data from 20 in-depth interviews with students and four teachers, and one focus group discussion with parents. The findings indicate that while deaf children experience minimal difficulty communicating with deaf peers, they face substantial challenges when interacting with hearing individuals, especially parents, grandparents, and others who lack sign language proficiency. Contributing factors include limited access to effective sign language instruction, insufficient sign language skills, and a scarcity of hearing individuals proficient in sign language. These barriers negatively affect both academic engagement and psychological well-being. The study highlights the need for comprehensive and coordinated support, including early medical intervention, access to hearing aids, strengthened sign language education, and the use of complementary communication strategies such as gestures and written communication. It also suggests an integrated medical, educational, and psychosocial intervention to address the deaf children’s need.